2022
DOI: 10.1038/s41430-022-01254-8
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt termination of vitamin C from ICU patients may increase mortality: secondary analysis of the LOVIT trial

Abstract: Background The LOVIT trial examined the effect of vitamin C on sepsis patients, and concluded that in adults with sepsis receiving vasopressor therapy in the ICU, those who received 4-day intravenous vitamin C had a higher risk of death or persistent organ dysfunction at 28 days than those who received placebo. The aim of this study was to determine whether the abrupt termination of vitamin C administration could explain the increased mortality in the vitamin C group. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…The LOVIT trial examined the effect of 4-day intravenous vitamin C administration on sepsis patients, and unexpectedly mortality was found to be elevated in the vitamin C group [ 155 ]. However, a secondary analysis showed that the increased mortality did not occur during vitamin C administration, but immediately after the abrupt termination of the vitamin [ 156 ]. A recent vitamin C for critically-ill COVID-19 patients trial observed similar harm from the abrupt termination of the 4-day vitamin C administration [ 157 , 158 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LOVIT trial examined the effect of 4-day intravenous vitamin C administration on sepsis patients, and unexpectedly mortality was found to be elevated in the vitamin C group [ 155 ]. However, a secondary analysis showed that the increased mortality did not occur during vitamin C administration, but immediately after the abrupt termination of the vitamin [ 156 ]. A recent vitamin C for critically-ill COVID-19 patients trial observed similar harm from the abrupt termination of the 4-day vitamin C administration [ 157 , 158 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent vitamin C for critically-ill COVID-19 patients trial observed similar harm from the abrupt termination of the 4-day vitamin C administration [ 157 , 158 ]. Rapid termination of vitamin C can lead to very low plasma levels through the rebound effect [ 156 ]. It even seems possible that the extra deaths after the sudden termination of vitamin C in the LOVIT trial might have been due to RHF since vitamin C deficiency increases the risk of RHF [ 1 – 11 ], and RHF is common in sepsis patients [ 159 , 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hemila ¨and Chalker conducted a secondary analysis of the LOVIT trial with the aim to determine whether the abrupt termination of high-dose vitamin C (''rebound effect'') could explain the increased mortality in the vitamin C arm [23]. Driven by a previous re-analysis of the CITRIS-ALI trial where the authors showed a time-dependent modification of the vitamin C effect by the termination of the vitamin treatment [24], Cox regression with two time periods to model the distribution of deaths over the first 11 days was used.…”
Section: Key Pointsmentioning
confidence: 99%
“…Second, it has been proposed that the signal for harm from administration of vitamin C as ascorbic acid in the LOVIT trial may not be due to the administration per se, but rather secondary to rebound effects on ascorbic acid cessation (7). In a post hoc Cox-risk regression analysis of LOVIT data, Hemilä et al (7) reported no difference in mortality between ascorbic acid and placebo during the 4-days of intervention (RR = 0.97 [95% CI, 0.65-1.44]) and significantly increased mortality in ascorbic acid group in the week postinfusion cessation RR = 1.9 (95% CI, 1.2-2.9; p = 0.004). They propose that the signal for harm may due to hypermetabolism of vitamin C on cessation leading to rebound reduction of plasma vitamin C to levels even lower than pretreatment levels (7).…”
mentioning
confidence: 99%